Nutrition interventions to treat low muscle mass in cancer. Issue 2 (8th January 2020) - Prado, Carla M.; Purcell, Sarah A.; Laviano, Alessandro
Abstract: Many patients with cancer experience poor nutritional status, which detrimentally impacts clinical outcomes. Poor nutritional status in cancer is primarily manifested by severe muscle mass (MM) depletion, which may occur at any stage (from curative to palliative) and often co‐exists with obesity. The objective of this article was to discuss gaps and opportunities related to the role of nutrition in preventing and reversing low MM in cancer. It also provides a narrative review of relevant nutritional interventions for patients capable of oral intake. The impact of nutrition interventions to prevent/treat low MM in cancer is not well understood, potentially due to the limited number of studies and of clinically viable, accurate body composition assessment tools. Additionally, the type of study designs, inclusion criteria, length of intervention, and choice of nutritional strategies have not been optimal, likely underestimating the anabolic potential of nutrition interventions. Nutrition studies are also often of short duration, and interventions that adapt to the metabolic and behavioural changes during the clinical journey are needed. We discuss energy requirements (25–30 kcal/kg/day) and interventions of protein (1.0–1.5 g/kg/day), branched‐chain amino acids (leucine: 2–4 g/day), β‐hydroxy β‐methylbutyrate (3 g/day), glutamine (0.3 g/kg/day), carnitine (4–6 g/day), creatine (5 g/day), fish oil/eicosapentanoic acid (2.0–2.2 g/day EPA and 1.5 g/day DHA), vitamin/minerals (e.g. vitamin D: 600–800 international units per day), and multimodal approaches (nutrition, exercise, and pharmaceutical) to countermeasure low MM in cancer. Although the evidence is variable by modality type, interventions were generally not specifically studied in the context of cancer. Understanding patients' nutritional requirements could lead to targeted prescriptions to prevent or attenuate low MM in cancer, with the overall aim of minimizing muscle loss during anti‐cancer therapy and maximizing muscle anabolism during recovery. It is anticipated that this will, in turn, improve overall health and prognostication including tolerance to treatment and survival. However, oncology‐specific interventions with more robust study designs are needed to facilitate these goals.